The Determinant Factors of Islamic Bank's Profitability in Indonesia During COVID-19 Pandemic (Sep 2019 - Sep 2021) - Sakina, Cynthia Farah (Muslim Business and Economics Review, 2022)
In this study, we to examine and analyse some factors that will determine Islamic banks profitability level in Indonesia. Some factors such as the influence of inflation, interest rates, NPF, FDR, and CAR will have an impact especially on profitability levels. In this study, we use the quantitative method. We selected the sample using purposive sampling method then referred to three Islamic banks in Indonesia. The data used in this paper were secondary data from the Central Bureau of Statistics (BPS), the Central Bank of Indonesia (BI), and related official websites of Islamic banks. We used the form of quarterly data for the last two years from September 2019 to September 2021. The results indicated that only NPF shows a significant effect on profitability (ROA) in Islamic banks.